The world underfoot : mosaics and metaphor in the Greek symposium - Franks, Hallie M. (Oxford University Press, 2018)
Drawing on discourses in the sociology and anthropology of space, the author presents an innovative new interpretation of pebble mosaic imagery as an active contributor to the ancient Greek symposium as a metaphorical experience.